2014
DOI: 10.1021/nl500022z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Efficient Light Absorption and Charge Separation in WO3/BiVO4 Core/Shell Nanowire Photoanode for Photoelectrochemical Water Oxidation

Abstract: We report a scalably synthesized WO3/BiVO4 core/shell nanowire photoanode in which BiVO4 is the primary light-absorber and WO3 acts as an electron conductor. These core/shell nanowires achieve the highest product of light absorption and charge separation efficiencies among BiVO4-based photoanodes to date and, even without an added catalyst, produce a photocurrent of 3.1 mA/cm(2) under simulated sunlight and an incident photon-to-current conversion efficiency of ∼ 60% at 300-450 nm, both at a potential of 1.23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
496
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 681 publications
(513 citation statements)
references
References 57 publications
14
496
2
1
Order By: Relevance
“…The values determined in this measurement are in good agreement with those reported in the literature 17, 75. The secondary electron emission spectra (SEE) of the WO 3 , BiVO 4 /WO 3 , BF 4 ‐treated MnO/BiVO 4 /WO 3 , Ca–EDTA‐treated MnO/BiVO 4 /WO 3 , and reference Au foil electrodes are displayed in Figure 4c.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The values determined in this measurement are in good agreement with those reported in the literature 17, 75. The secondary electron emission spectra (SEE) of the WO 3 , BiVO 4 /WO 3 , BF 4 ‐treated MnO/BiVO 4 /WO 3 , Ca–EDTA‐treated MnO/BiVO 4 /WO 3 , and reference Au foil electrodes are displayed in Figure 4c.…”
Section: Resultssupporting
confidence: 89%
“…The BF 4 ‐treated MnO/BiVO 4 /WO 3 anode achieved 6.25 mA cm −2 at the 1.23 V versus RHE. We emphasize that the photocurrent of BF 4 ‐treated MnO attached to the BiVO 4 /WO 3 anode is the highest of the previously reported BiVO 4 ‐based photoanodes with hole scavenger for solar water splitting, as shown in Table S2 and Figure S4 (Supporting Information) 13, 14, 16, 17, 21, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69. Otherwise, Ca–EDTA‐treated MnO NPs/BiVO 4 /WO 3 recorded the lowest photocurrent density of about 2.5 mA cm −2 .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The adjustable species and ratios of metal ions in LDHs make the LDHs the promising candidates as OECs in PEC devices. Considering that the outstanding performance can be achieved through using un-doped porous BiVO4 film as only photon absorber and nanostructured LDHs as OECs, further improvement of the PEC cell efficiency is expected when various strategies of tuning the compositions [16] or forming heterojunctions [29,40,60] and tandem cells [18,46] are used to enhance absorption and photogenerated carriers' separation of semiconductors. Therefore, our work could provide a new strategy to fabricate composite photoanodes effectively promoting charge utilization and the surface reaction kinetics for PEC water splitting and other solar-to-fuel energy conversion applications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, integrating BiVO4 with LDH as composite photoanode for highly efficient PEC water splitting is still a great challenge. Moreover, many reports have shown that ingenious photoanodes with improved separation of photogenerated charge carriers can be obtained through fabricating various nanostructures (such as ordered nanorod arrays [5], porous films [13], and heterogeneous nanoarrays [27][28][29][30][31][32]). Notably, the nanostructured electrocatalysts which can be used as OECs demonstrate many special features, such as more active sites, superhydrophilic and superaerophobicity [33][34][35].…”
Section: Introductionmentioning
confidence: 99%